Analisa Mubadalah Hadis “Fitnah Perempuan” dan Implikasinya terhadap Relasi Gender (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2021)
Problems that have always been discussed up to now are gender and issues regarding the inequality of relations between women and men. Apart from the Qur'an, Hadith is also accused of being a contributor to discriminating against women. The understanding of the ulama also seems taken for granted in justifying a form of discrimination, so that the relationship between men and women becomes unstable with one another. In this study, the aim of this research is to understand religious texts and focus on the hadiths which can provide a balanced interpretation offer that does not defend either party. This study uses the mubadalah approach as an analysis knife. The conclusion of this research is that the hadith regarding “women's slander” is not something that can legalize discrimination by using stereotypes against one of them. But further than that the text suggests both men and women to be aware of each other from all possible slander ( charm) that both of them could evoke.
Keywords: Gender Relations; Slander; Mubadalah.